(untitled) (Texas Journal of Medical Science, 2022)
The coronavirus disease of 2019 has fast spread over the world, posing a serious threat to human health. This epidemic is extremely stressful for healthcare workers in general, and nurses in particular, because they are at the vanguard of the worldwide struggle against COVID-19. Aims: Assessment of the Nurses’ (Participating in Courses Related to Coronavirus Disease) knowledge Regarding Nature and Complications of Coronavirus